FDA Approval Summary: Atezolizumab or Pembrolizumab for the Treatment of Patients with Advanced Urothelial Carcinoma Ineligible for Cisplatin‐Containing Chemotherapy - Suzman, Daniel L. (Oncologist, 2018)
The U.S. Food and Drug Administration (FDA) granted accelerated approval to atezolizumab and pembrolizumab in April and May 2017, respectively, for the treatment of patients with locally advanced or metastatic urothelial carcinoma who are not eligible for cisplatin‐containing chemotherapy. These approvals were based on efficacy and safety data demonstrated in the two single‐arm trials, IMvigor210 (atezolizumab) and KEYNOTE‐052 (pembrolizumab). The primary endpoint, confirmed objective response rate, was 23.5% (95% confidence interval [CI]: 16.2%–32.2%) in patients receiving atezolizumab and 28.6% (95% CI: 24.1%–33.5%) in patients receiving pembrolizumab. The median duration of response was not reached in either study and responses were seen regardless of PD‐L1 status. The safety profiles of both drugs were generally consistent with approved agents targeting PD‐1/PD‐L1. Two ongoing trials (IMvigor130 and KEYNOTE‐361) are verifying benefit of these drugs. Based on concerning preliminary reports from these trials, FDA revised the indications for both agents in cisplatin‐ineligible patients. Both drugs are now indicated for patients not eligible for any platinum‐containing chemotherapy or not eligible for cisplatin‐containing chemotherapy and whose tumors/infiltrating immune cells express a high level of PD‐L1. The indications for atezolizumab and pembrolizumab in patients who have received prior platinum‐based therapy have not been changed. This article summarizes the FDA thought process and data supporting the accelerated approval of both agents and the subsequent revision of the indications. IMPLICATIONS FOR PRACTICE. The accelerated approvals of atezolizumab and pembrolizumab for cisplatin‐ineligible patients with advanced urothelial carcinoma represent the first approved therapies for this patient population. These approvals were based on single‐arm trials demonstrating reasonable objective response rates and favorable durations of response with an acceptable toxicity profile compared with available non‐cisplatin‐containing chemotherapy regimens. However, based on concerning preliminary reports from two ongoing phase III trials, the FDA revised the indication for both agents in cisplatin‐ineligible patients. Both are now indicated either for patients not eligible for any platinum‐containing chemotherapy or not eligible for cisplatin‐containing chemotherapy and whose tumors have high expression of PD‐L1.